The importance of empty spaces in cities and a proposed set of tools to support their use - Pluta, Agata (Znaczenie pustych przestrzeni w miastach i propozycja narzędzi wspierających ich wykorzystanie, 2019)
The progressive urbanism and population density of the modern world, along with the degradation of the natural environment, have caused a radical disappearance of vacant urban spaces. For this reason the importance of undeveloped, open spaces located in urban areas has increased. The development potential of empty spaces should be reasonably assessed, and thereby their use should be considered − as an element of compact urban fabric or a reserve of space for the future. The goal of the article is to discuss and evaluate the role of empty areas in cities in terms of economic, social and environmental impacts, as well as to provide a universal toolset in the field of spatial planning that can be utilized to secure the value, and maintain control over the management of empty spaces. The object of the study is Wroclaw with particular emphasis on undeveloped urban land. The research covered, depending on the available data, the period 2010-2018. The work uses a deductive method, simple statistical methods, results of research carried out so far and a reinterpretation of available scientific literature. The article is an introduction to considerations on the impact of empty urban spaces on the socio-economic development of modern cities
Biblioteka Regionalisty, 2019, Nr 19, s. 168-179
Keywords: Dolny Śląsk